The Flickering of Jackie Chan: Transnational Chinese Film Stardom, Web 2.0, and the Signification of Performance. - Lau, Dorothy Wai-Sim (International Journal of the Humanities, 2010)
Transnational currency, mobile image low and proliferation of new-media applications profoundly alter the cultural preoccupations of how stars are represented and understood. Flickr , part of the glossary of Web 2.0, has lifted barriers in the circulation of images and it invites new forces and tensions to the interplay between stars, enactment and users. Issues become riveting when considering Web 2.0 in relation to the phenomenal influx of Chinese film talents to Hollywood as a border-crossing event. Jackie Chan, a highly celebrated transnational star among others, is taken to be a case-in-point that speaks directly to the concerns of online stardom on image-sharing sites and alternative star-audience dynamics. Through posting photographs onto the site, Chan' characteristic acrobatic presence, exceeding the film texts, is manipulated by the velocity of grass-root participation. Chan' image is compelling yet ambivalent when hypothesized with respective to "Chinese-ness" and "global-ness" which illustrate the ways his performance agency can possibly function in participatory cultural politics. Writing Chan as a sign that entails transnational polemics in the framework of star-as-performer, this paper sheds light on re-conceptualizing stardom in electronically-mediated settings as volatile, contested and proliferating as it can ever be.